Emmanuel Macron's "New Way": Setting the course for re-election in 2022 - Ronja Kempin; Dominik Rehbaum (Stiftung Wissenschaft und Politik (SWP), 2020)
French President Emmanuel Macron wants to be reelected in 2022. In view of citizens' disenchantment with the political and social order of their country and the consequences of the Corona pandemic, the president feels compelled to embark on a 'new way'. This new approach has three components: a move away from the policy of budget consolidation, a political positioning within the neoliberal-conservative faction of the political spectrum, and greater proximity to the people. If Macron receives interim support from the European Union (EU) to cushion the consequences of Covid-19 for France's economic and social system, he should be able to strengthen reform forces at home and enable France to broker compromises on vital subjects concerning EU reform.
Keywords: 320